Choroidal Morphology on Ultra-Widefield Indocyanine Green Angiography and Response to Aflibercept in Pachychoroid Neovasculopathy - Su Yeon Han; Seung Hoon Lee; Phil-kyu Lee; Ho Ra; Jiwon Baek (Pharmaceuticals, 2023)
Purpose: This study assessed the relationship between the choroidal morphology and short-term response to aflibercept treatment in pachychoroid neovasculopathy (PNV). Methods: This was a retrospective case-control study. Ultra-widefield indocyanine green angiography (UWICGA) and optical coherence tomography (OCT) images of 90 PNV eyes of 90 patients treated with aflibercept were enrolled. Responsiveness to aflibercept was defined as a complete resolution of sub- or intra-retinal fluid after three loading doses (50 dry and 40 non-dry eyes). Subfoveal choroidal thickness (SFCT) was measured on OCT images, and choroidal vessel density (CVD), CVD asymmetry, intervortex anastomosis, and choroidal vascular hyperpermeability (CVH) were assessed on UWICGA images. Results: CVD on UWICGA differed between groups in terms of the total area (0.323 ± 0.034 in dry vs. 0.286 ± 0.038 in non-dry, p < 0.001) and area of each quadrant (superotemporal: 0.317 ± 0.040 vs. 0.283 ± 0.040, superonasal: 0.334 ± 0.040 vs. 0.293 ± 0.045, inferonasal: 0.306 ± 0.051 vs. 0.278 ± 0.052, inferotemporal: 0.334 ± 0.047 vs. 0.290 ± 0.046; all p ≤ 0.010). The CVH grade differed between groups (mean 1.480 ± 0.735 vs. 1.875 ± 0.822, p = 0.013). ST and IT intervortex anastomoses were common in the dry group, while SN, ST, and IT were most common in the non-dry group (p = 0.001). Conclusions: A poor short-term response to aflibercept treatment in PNV eyes was associated with a lower Haller vessel density, higher CVH grade, and intervortex anastomosis involving more quadrants on UWICGA.